1986
DOI: 10.1149/1.2108709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molybdenum on the Pitting Corrosion of Aluminum Films

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…According to Hu et al, 42 the structure of surface molybdenum oxides present on Al 2 O 3 under ambient conditions consists of polymeric species (Mo 7 O 24 6− and Mo 8 O 26 4− ) at high Mo loadings. In addition, Spevack et al found evidence of multivalent (Mo(IV), Mo(V), and Mo(VI)) species within molybdenum oxide films supported on alumina and graphite.…”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hu et al, 42 the structure of surface molybdenum oxides present on Al 2 O 3 under ambient conditions consists of polymeric species (Mo 7 O 24 6− and Mo 8 O 26 4− ) at high Mo loadings. In addition, Spevack et al found evidence of multivalent (Mo(IV), Mo(V), and Mo(VI)) species within molybdenum oxide films supported on alumina and graphite.…”
Section: 43mentioning
confidence: 99%
“…[21][22][23] The impact of molybdate on the corrosion resistance of aluminum has been explored extensively in the literature. 21,[24][25][26][27][28][29][30][31][32][33][34] Molybdate improves the pitting resistance of aluminum and its alloys by increasing the pitting potential to more noble values with respect to the opencircuit potential. 28 However, the extent of inhibition is highly dependent on the ratio of molybdate to chloride ion concentration.…”
mentioning
confidence: 99%
“…Several different mechanisms have been proposed to explain the passivity of stainless aluminum alloys, including electrostatic repulsion of Cl" by oxidized solute atoms [1][2][3], formation of an oxidized solute barrier layer [3,4], blockage of Cl" transport through the passive film [22], stabilization of the passive film oxide structure [6], replacement of oxidized Al in the passive film by oxidized solute to form a more stable oxide [28,29], reduction of the critical pH for pit propagation [17][18][19][20], and reduction in C1-adsorption due to pHpzc changes [11][12][13][14][15]. Additionally, Macdonald and coworkers [34,35] studying Mo-and W-containing stainless steels have proposed a solutevacancy interaction model (SVIM).…”
Section: Passivity Mechanism Backgroundmentioning
confidence: 99%
“…The SRIM explains why mechanisms involving properties of an oxidized solute passive film, such as barrier layer formation [1][2][3][4]22,28,29], pHpzc reduction [11][12][13][14][15], and solubility reduction in low-pH environments [17][18][19][20], can appear to account for the enhanced passivity of these alloys despite the fact that the passive film is at least half oxidized or hydrated aluminum and can be almost entirely oxidized or hydrated aluminum, depending on the alloy system and the polarization conditions. The important factor is the solute's localized concentration at the interphase and in occluded cells, not the overall concentration of the solute in the passive film.…”
Section: Passivity Mechanismmentioning
confidence: 99%
See 1 more Smart Citation